Habituation and Connectionism of Islamic Education at Integrated Islamic Elementary Schools in Indonesia - Muhammad Yusuf; Sani Fitri Nur Laela; Rahmat Hariyadi (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
This study aims to determine the concept of PAI learning in elementary schools; the concept of learning theory of behaviorism by E.L. Thorndike; and how is Torndike’s theory of behaviorism implemented in PAI learning at the elementary level. The research methodology used in the preparation of this article is a qualitative research method. Sources of data are obtained by collecting facts in the field through observation and interviews. The data analysis technique is the triangulation technique which includes the stages of data presentation, data reduction, and concluding. The results showed that: 1) Elementary school PAI subjects had their curriculum with the content of the Qur’an, creed, worship, morality, fiqh, and SKI. 2) learning theory of behaviorism E.L. Thorndike is often known as connectionism, which is a learning theory that focuses on stimulus and response in the learning process. 3) implementation of behavioristic learning theory that can be applied to PAI learning at SDIT Alam Al-Hikmah Magelang, among others, providing motivation, encouragement, practice questions, or rewards and punishments when educators/teachers carry out teaching and learning activities on religious materials such as tahfidz, and funeral prayer.